PENGARUH HARGA, KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA PT. JALUR NUGRAHA EKAKURIR (JNE) - Frendy Setiawan (2021)
This research is a quantitative research with the aim of proving and analyzing the effect of price, service quality and brand image on purchasing decisions at PT. The Nugraha Ekakurir (JNE) line. The population used in the study was or was using JNE expedition services in the East Jakarta area. The sample used was 100 respondents with non-probability sampling method and purposive sampling type and then for data collection using a Likert scale and through distributing questionnaires. The data analysis technique used in this study is the Partial Least Square (PLS) method. The results of this study, price and brand image variables have a significant and significant effect on purchasing decisions, while the service quality variable has no and no significant effect on purchasing decisions.